What We Spend and What We Get: Public and Private Provision of Crime Prevention - Ann Dryden Witte
In this paper, we consider a number of issues regarding crime prevention and criminal justice. We begin by considering how crime is measured and present both general and specific evidence on the level of crime in a variety of countries. Crime is pervasive and varies substantially across countries. We outline the arguments for some public roll in crime prevention, enforcement, prosecution, defence, and adjudication. We consider the relative role of the public and private sectors in crime control and criminal justice. We discuss various measures for the effectiveness of the criminal justice system. We conclude by suggesting some potential areas for research.